The aims of expanded universal carrier screening: Autonomy, prevention, and responsible parenthood - Hout, Sanne van der (Bioethics, 2019)
Expanded universal carrier screening (EUCS) entails a population-wide screening offer for multiple disease-causing mutations simultaneously. Although there is much debate about the conditions under which EUCS can responsibly be introduced, there seems to be little discussion about its aim: providing carrier couples with options for autonomous reproductive choice. While this links in with current accounts of the aim of foetal anomaly screening, it is different from how the aim of ancestry-based carrier screening has traditionally been understood: reducing the disease burden in the population. The reasons why the aim of EUCS is presented in terms of ‘autonomy’ rather than ‘prevention’ have not been spelled out in the literature. This paper seeks to fill this gap by considering the morally relevant similarities and dissimilarities between foetal anomaly screening, ancestry-based carrier screening and EUCS. When carrier screening is performed in the prenatal period, enhancing autonomy appears the most appropriate aim of EUCS, as the alternative of ‘prevention through selective abortion’ would urge women to terminate wanted pregnancies. However, when screening is conducted in the preconception period, carrier couples can avoid the birth of affected children by other means than selective abortion, for instance preimplantation genetic diagnosis. To the extent that this increased control over passing on a genetic disorder raises questions of parental responsibility, it seems necessary that the account of the aims of EUCS is wider than only in terms of enhancing reproductive autonomy.